Prunus mira Koehne in Sichuan, China: Recorded History as a Medicine and Food, Modern Applications, Distribution, and Ethnobotanical Investigations - Zhang, Jingwen; Chen, Wanyue; Sun, Weijun; Zhou, You; Li, Xiaoli; Zhang, Jing; Fan, Gang; Yin, Hongxiang; Qin, Ju; Yuan, Yongcui; Xu, Wei; Wang, Zhang (Frontiers in Pharmacology, 2022)
Prunus mira Koehne, a Prunus plant in the Rosaceae family, is named ཁམབུ། in Tibetan and “Guang he tao” in Chinese. It is mainly distributed in Tibet Autonomous Region, Yunnan Province, and Sichuan Province in China. It is also a rare “living fossil group” of peach genetic resources in the world. It is used in traditional Chinese medicine for the treatment of dysmenorrhea, injury, intestinal dryness, constipation, and other diseases, and is used in Tibetan medicine for the treatment of hair, eyebrows, and beard shedding. In this article, the botanical characteristics, medicinal history, modern applied research, and ethnobotanical investigation of P. mira were recorded and evaluated. P. mira was first recorded in Dumu Materia Medica. P. mira in Sichuan Province is mainly distributed in Ganzi Tibetan Autonomous Prefecture, and has certain economic and medicinal value. P. mira has high nutritional composition. It is made into high-quality edible oil, cosmetic base oil, fruit juice, fruit wine, fruit vinegar, “Liang guo”, and other products. Oleic acid and linoleic acid are the main fat-soluble components of P. mira, which has an anti-inflammatory medicinal value and promotes hair growth. Its longevity and cold resistance can bring great genetic value and play an important role in maintaining peach genetic diversity. At present, there are few studies on the pharmacological effects of specific active components of P. mira and there are also few clinical studies. We can continue to study these aspects in the future. At the same time, products of P. mira have great market potential. All in all, P. mira is very worthy of further research and development.